Genotypic and phenotypic characteristics of Candida parapsilosis bloodstream isolates: Health Care Associated Infections in a teaching Hospital in Italy - Giuseppina Caggiano; Simona Fioriti; Gianluca Morroni; Francesca Apollonio; Francesco Triggiano; Gloria D'Achille; Pasquale Stefanizzi; Lidia Dalfino; Luigi Ronga; Adriana Mosca; Eleonora Sparapano; Carmela De Carlo; et al. (Elsevier, 2024)
Background: Candidemia is the most common healthcare associated invasive fungal infection. Over the last few decades, candidemia caused by Candida species other than Candida albicans, particularly the Candida parapsilosis complex, has emerged worldwide. The aims of this study were: to analyze the genotypic and phenotypic characteristics of C. parapsilosis strains isolated from blood cultures and the environment in a hospital in southern Italy, to study the possible source of infection and to correlate the isolated strains. Methods: From April to October 2022, cases of candidemia due to C. parapsilosis in patients admitted to a hospital in the Apulia region were investigated. However, 119 environmental samples from the intensive care unit were collected for identification of the likely environmental reservoir of infection. Routine antifungal (amphotericin B, anidulafungin, fluconazole) susceptibility was performed on all isolates. Whole genome sequencing was performed to study the genotypic correlation of the isolates. Biofilm biomass and metabolic activity were also quantified for all isolates. Results: A total of 43 C. parapsilosis isolates were cultured from the bloodstream of each patient in different departments, and seven surface samples were positive for C. parapsilosis. Most of the isolated yeasts (41/50; 85 %) were resistant to fluconazole and were genetically related to each other, suggesting an ongoing clonal outbreak of this pathogen. The fluconazole-susceptible isolates produced significantly more biofilm than did the resistant isolates. Metabolic activity was also higher for fluconazole-susceptible than resistant isolates. Conclusion: Cross-transmission of the microorganisms is suggested by the phenotypic similarity and genetic correlation between clinical and environmental strains observed in our study.